2021
DOI: 10.1371/journal.pntd.0008968
|View full text |Cite
|
Sign up to set email alerts
|

Total Phenolic Fraction (TPF) from Extra Virgin Olive Oil: Induction of apoptotic-like cell death in Leishmania spp. promastigotes and in vivo potential of therapeutic immunomodulation

Abstract: Background Leishmaniasis is a serious multifactorial parasitic disease with limited treatment options. Current chemotherapy is mainly consisted of drugs with serious drawbacks such as toxicity, variable efficacy and resistance. Alternative bioactive phytocompounds may provide a promising source for discovering new anti-leishmanial drugs. Extra Virgin Olive Oil (EVOO), a key-product in the Mediterranean diet, is rich in phenols which are associated with anti-inflammatory, anti-cancer and anti-microbial effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 93 publications
2
12
0
1
Order By: Relevance
“…OLEO exhibited an inhibitory effect in vitro against both the promastigote and intracellular amastigote forms of L. major parasites. These results are in accordance with our previous studies, indicating an OLEO-enriched phenolic fraction with a powerful inhibitory effect against L. major promastigotes and amastigotes 10 . Additionally, these data are in line with a recent study also demonstrating a powerful inhibitory effect of another natural product, 6-gingerol, against L. major promastigotes 23 .…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…OLEO exhibited an inhibitory effect in vitro against both the promastigote and intracellular amastigote forms of L. major parasites. These results are in accordance with our previous studies, indicating an OLEO-enriched phenolic fraction with a powerful inhibitory effect against L. major promastigotes and amastigotes 10 . Additionally, these data are in line with a recent study also demonstrating a powerful inhibitory effect of another natural product, 6-gingerol, against L. major promastigotes 23 .…”
Section: Discussionsupporting
confidence: 94%
“…The segregation of IgG2a and IgG1 isotypes has been extensively used as a surrogate marker of protective Th1 and exacerbating Th2 responses, respectively 37 . These findings are in accordance with our previous study where mice treated with the OLEO-enriched phenolic fraction also exhibited a higher IgG2a/IgG1 ratio 10 . The prevalence of Th1 immunity after treatment with OLEO was further validated by the induced IL-12 cytokine 38 .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Outras propriedades dos compostos bioativos presentes no azeite de oliva se referem a melhor liberação de insulina pósprandial (Sanchez-Rodriguez et al, 2021), regulação do metabolismo e resistência muscular (Luzi et al, 2021), neuroprotetor aliviando disfunção cognitiva no Alzheimer (Qin et al, 2021), efeito anti-leishmaniose (Karampetsou et al, 2021).…”
Section: Journal Of Foodunclassified
“…Our group has showcased the anti-leishmanial properties of olive oil phenolic compounds by demonstrating that pure oleuropein and oleocanthal (OLEO) exert anti-leishmanial properties in vitro and promote in vivo efficacy in murine experimental models of VL and CL [ 23 , 24 , 25 , 26 ]. In addition, we have reported that TPF exhibits chemotherapeutic anti-leishmanial activity in vitro and in vivo [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%